SHALAWAT PERSPEKTIF TAFSIR SUFI : Studi Komparasi Tafsir Al-Jailani dan Tafsir Lathaif Al-Isyarat - Suryana Alfathah (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
This article aims to discuss two Sufi interpretations, namely al Jailani's interpretation by Syekh Abdul Qadir al Jailani and al Qusyairi's interpretation of Lathaif al Isyarat on the interpretation of QS. Al-Ahzab: 56 regarding blessings. The discussion includes the terminology of shalawat, the biographies of al Jailani and al Qusyairi, the characteristics of al Jailani's interpretation and al Qusyairi's interpretation, as well as the results of a comparison between the two. This research is included in qualitative research with literature study method. As well as the muqaran method in the analysis process. The results of this study are that in the interpretation of QS. Al Ahzab: 56 there are similarities and differences between the interpretations of al Jailani and al Qusyairi. The similarities are found on the side of the book of interpretation, in the form of sources, methods, and ittijah. The difference is in the purpose of writing, the meaning of the sign, and the style of language. Al Jailani aims to liberate the minds of the younger generation from moral decline as well as trying to uncover the meanings of the contents of the Koran. Meanwhile, al Qusyairi aims to reveal the meanings of the Koran according to ma'rifat experts in a concise manner so as not to be boring. In QS. Al Ahzab: 56, al Jailani places more emphasis on the obligation to pray to the Prophet SAW as a form of respect and exaltation. Meanwhile, al Qusyairi mentions that prayer is a tribute as well as asking for intercession from the Prophet SAW. Al Jailani's language style is more assertive in terms of the purpose of writing, while al Qusyairi is softer based on the purpose of writing.